Isotopic Tracers Suggest Limited Trans-Oceanic Movements and Regional Residency in North Pacific Blue Sharks (Prionace glauca) - Madigan, Daniel J.; Shipley, Oliver N.; Carlisle, Aaron B.; Dewar, Heidi; Snodgrass, Owyn E.; Hussey, Nigel E. (Frontiers in Marine Science, 2021)
Blue sharks (Prionace glauca) are globally distributed, large-bodied pelagic sharks that make extensive migrations throughout their range. In the North Pacific, mark-recapture studies have shown trans-Pacific migrations, but knowledge gaps in migration frequency hinder understanding of regional connectivity and assessments of regional demography for stock assessments. Here, we use oceanographic gradients of stable isotope ratios (i.e., regional isoscapes) to determine exchange rates of blue sharks between the East and West North Pacific Ocean (EPO and WPO). We generated regional δ13C and δ15N distributions for blue sharks from published values in the North Pacific (n = 180; both sexes, juveniles and adults combined). Discriminant analysis suggested low trans-Pacific exchange, categorizing all western (100%) and most eastern (95.3%) blue sharks as resident to their sampling region, with isotopic niche overlap of WPO and EPO highly distinct (0.01–5.6% overlap). Limited trans-Pacific movements suggest that other mechanisms maintain genetic mixing of the North Pacific blue shark population. Potential finer scale movement structure was indicated by isotopic differences in sub-regions of the eastern and western Pacific, though application of mixing models are currently due limited by aberrantly low blue shark δ13C values across studies. Our results suggest that blue shark population dynamics may be effectively assessed on a regional basis (i.e., WPO and EPO). We recommend further studies to provide size- and sex-specific movement patterns based on empirical isotopic values with large sample sizes from targeted regions. Strategically applied stable isotope approaches can continue to elucidate migration dynamics of mobile marine predators, complementing traditional approaches to fisheries biology and ecology.